2020
DOI: 10.37929/nveo.704056
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Content and Compositions of Naturalized Tagetes minuta L. (Wild marigold)

Abstract: Tagetes minuta L. known as Muster John Henry is an annual, fragrant and naturalized plant species in Turkey. The study aimed to determine essential oil content and components of Tagetes minuta L. from the flora of Hatay. Flower and leaf parts were hydrodistilled together in the full flowering period. Essential oils were analysed by gas chromatography-mass spectrometry. Essential oil content was found at 1.8%. Essential oil compositions that constitute 99.20% of the essential oil were revealed. Main components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Previously, dihydrotagetone, ( E )-β-ocimene, ( E )-tagetone, ( Z )-tagetone, and ( Z )-ocimenone have been identified in the essential oils in varying concentrations from the aerial parts of T. minuta. , In the current study, we identified these compounds in the root volatiles of T. minuta, showing similarities in foliar and root chemistry.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Previously, dihydrotagetone, ( E )-β-ocimene, ( E )-tagetone, ( Z )-tagetone, and ( Z )-ocimenone have been identified in the essential oils in varying concentrations from the aerial parts of T. minuta. , In the current study, we identified these compounds in the root volatiles of T. minuta, showing similarities in foliar and root chemistry.…”
Section: Resultsmentioning
confidence: 52%
“…Compounds that were only identified in B. pilosa include ethyl isobutyrate, nonane, tridecane, and silphiperfol-5-ene, while heptadecane, isopropyl tetradecanoate, and isopropyl palmitate were exclusively detected in Previously, dihydrotagetone, (E)-β-ocimene, (E)-tagetone, (Z)-tagetone, and (Z)-ocimenone have been identified in the essential oils in varying concentrations from the aerial parts of T. minuta. 41,46 In the current study, we identified these compounds in the root volatiles of T. minuta, showing similarities in foliar and root chemistry. Our results agree with previous studies, which identified γ-terpinene, silphiperfol-5-ene, presilphiperfol-7-ene, silphinene, modheph-2-ene, (E)-caryophyllene, (E)-β-farnesene, α-isocomene, β-isocomene, and β-patchoulene in the headspace volatiles of fresh roots of A. annua.…”
Section: ■ Materials and Methodsmentioning
confidence: 56%
“…Researchers have discovered that the marigold flower's flavonoids have anti-inflammatory, cytotoxic, and inhibitory effects on colon cancer, leukemia, and melanoma cells. Marigold is frequently used in pharma industry due to its numerous therapeutic properties [3,108,109].…”
Section: Industrial Applications Of Luteinmentioning
confidence: 99%